Trefftz and fundamental solution-based finite element methods - Qin, Qing-Hua (Bentham Books, 2021)
This reference explains hybrid-Trefftz finite element method (FEM). Readers are introduced to the basic concepts and general element formulations of the method. This is followed by topics on non-homogeneous parabolic problems, thermal analysis of composites, and heat conduction in nonlinear functionally graded materials. A brief summary of the fundamental solution based-FEM is also presented followed by a discussion on axisymmetric potential problems and the rotordynamic response of tapered composites. The book is rounded by chapters that cover the n-sided polygonal hybrid finite elements and analysis of piezoelectric materials.Key Features- Systematic presentation of 9 topics- Covers FEMs in two sections: 1) hybrid-Trefftz method and 2) fundamental FEM solutions- Bibliographic references- Includes solutions to problems in the numerical analysis of different material types- Includes solutions to some problems encountered in civil engineering (seepage, heat transfer, etc).This reference is suitable for scholars involved in advanced courses in mathematics and engineering (civil engineering/materials engineering). Professionals involved in developing analytical tools for materials and construction testing can also benefit from the methods presented in the book.